2017
DOI: 10.1073/pnas.1708341114
|View full text |Cite
|
Sign up to set email alerts
|

GATA2/3-TFAP2A/C transcription factor network couples human pluripotent stem cell differentiation to trophectoderm with repression of pluripotency

Abstract: SignificanceThis study provides a mechanistic explanation for the differentiation of trophoblasts from human pluripotent stem cells, a process relying on BMP morphogens. We found that a network of the transcription factors GATA2, GATA3, TFAP2A, and TFAP2C regulates early trophoblast progenitor specification by activating placental genes and inhibiting the pluripotency gene OCT4, thus acting to couple trophoblast specification with exit from pluripotency. To demonstrate the relevance of our findings in vivo, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
178
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(186 citation statements)
references
References 88 publications
(111 reference statements)
7
178
0
1
Order By: Relevance
“…Characterisation of such hESC-derived trophoblast cells using our four putative trophoblast criteria is incomplete, but it has been shown that these cells exhibit partial (but not complete) hypomethylation of the ELF5 promoter and downregulate some of the C19MC complex microRNAs (Lee et al, 2016a). The formation of SCT that secretes human chorionic gonadotropin (hCG) and expresses the EVT marker, HLA-G, as well as other genes expressed by trophoblast, such as KRT7, GATA2/3 and TCFAP2A/C, has also been reported (Amita et al, 2013;Horii et al, 2016;Krendl et al, 2017). However, transcriptomic analysis of such hESC-derived trophoblast reveals that these cells are different from both term trophoblast and mesoderm lineages; this has been a subject of discussion as some markers are expressed in both cell types (Bernardo et al, 2011;Jain et al, 2017).…”
Section: Human Embryonic Stem Cell-derived Trophoblast Cellsmentioning
confidence: 84%
“…Characterisation of such hESC-derived trophoblast cells using our four putative trophoblast criteria is incomplete, but it has been shown that these cells exhibit partial (but not complete) hypomethylation of the ELF5 promoter and downregulate some of the C19MC complex microRNAs (Lee et al, 2016a). The formation of SCT that secretes human chorionic gonadotropin (hCG) and expresses the EVT marker, HLA-G, as well as other genes expressed by trophoblast, such as KRT7, GATA2/3 and TCFAP2A/C, has also been reported (Amita et al, 2013;Horii et al, 2016;Krendl et al, 2017). However, transcriptomic analysis of such hESC-derived trophoblast reveals that these cells are different from both term trophoblast and mesoderm lineages; this has been a subject of discussion as some markers are expressed in both cell types (Bernardo et al, 2011;Jain et al, 2017).…”
Section: Human Embryonic Stem Cell-derived Trophoblast Cellsmentioning
confidence: 84%
“…Mesoderm was represented by differentiating MSCs to adipocytes and osteocytes, lateral mesoderm to cardiomyocytes, and intermediate mesoderm to nephron progenitors and matured nephrons; definitive endoderm cells were differentiated to hepatocytes and lung progenitors; NSCs, which belong to ectoderm, were differentiated to motor neurons and astrocytes, and cortical neuron progenitors were cultured to a mature state; neural crest progenitors, which give rise to multiple lineages that migrate throughout the body [24], were produced from neurospheres [25]. Extraembryonic tissues were represented by trophoblast progenitors differentiated from hPSCs [26], and myotubes, keratinocytes, and fibroblasts were derived from primary tissues ( Fig. 1a).…”
Section: Atlas Of Paraspeckle Trajectories During Cell Fate Transitionsmentioning
confidence: 99%
“…All differentiation experiments were carried out with H9 cells, except lung progenitor and cortical neuron differentiation, which were performed with iPSC lines, namely NKX2.1-P2A-eGFP [57] and foreskin fibroblast-derived iPSCs [58], respectively. For paraspeckle measurements in trophoblast progenitors and neural crest cells, we used differentiation protocols, as previously described [26,59].…”
Section: Psc Culturementioning
confidence: 99%
“…In their study, they have not only confirmed the essential role played by GATA3 during TE specification through in vitro assays based on human pluripotent stem cells, but they have also assessed the in vivo role of GATA3 in embryonic development in primates through microinjection of GATA3 morpholino antisense oligonucleotides into zygotes of rhesus macaques. Zygotes were differentiated in vitro and analyzed, which revealed embryonal arrest at the 32-cell morula state [117]. This approach combines stem cell technology with classical animal models in a so far unprecedented way.…”
Section: Thoughts On the Limitations And Promises Of The Continuouslymentioning
confidence: 99%